Eksistensi Sompa sebagai Representasi Kelas Sosial dalam Perkawinan Adat Bugis Soppeng Perspektif Hukum Islam - Adam, Aldi; Baldan Haramain, Fathur (Jurnal El-Thawalib, 2025)
This study is based on the reality of the Bugis Soppeng community. Where the community has customs or habits in giving a dowry called Sompa. Like dowries in general, Sompa is also given at the time of the contract or after the contract. However, in the provisions of Sompa, social strata is the main reference in the amount of property that must be given by the groom to the bride. The purpose of this study is to examine how to determine sompa based on the social strata of the Bugis Soppeng tribe. This study is a qualitative study with a descriptive-analytical type, which uses primary data in the form of interviews with three informants, namely traditional leaders, religious leaders, and traditional community actors, as well as secondary data in the form of literature, traditional documents, and Islamic law references. Data collection techniques are carried out through observation, in-depth interviews, and documentation. Furthermore, data analysis is carried out qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of this study indicate that Sompa based on social stratification in the Bugis Soppeng community is based on several factors including heredity, wealth, education, position, and honor. The size of Sompa depends on the social strata of the woman and her parents. In Islamic Law, the size of the dowry is not determined by a maximum limit. The size used by the Bugis Soppeng community is a customary size, where the practice of sompa' is a negotiation between the man and the woman and there is no coercion. In other words, it does not contradict Islamic Law. Based on the concept of al-'Adah Muhakkamah, customary practices can be accepted as long as they do not conflict with Islamic Law.